Construction Value Chains and Their Productivity Growth - Tero Kuusi; Juha-Matti Junnonen; Martti Kulvik (The Research Institute of the Finnish Economy (ETLA), 2020)
The construction industry has suffered from low growth in recent decades. Motivated by the economic impor-tance of the industry, we revisit the construction produc-tivity puzzle by analyzing the construction value chains of 12 European countries with data from the World In-put-Output and EU KLEMS databases. We decompose construction-related value-added and productivity con-tributions to the construction industry and the rest of the value chain, and show that the traditional focus on the construction industry is restrictive. There is a substantial amount of construction-related value-add-ed generated in other industries, and the productivi-ty growth in the construction value chains has, for the most part, been seen in them. Furthermore, we show that there is a strong, long-term relationship between construction-related patents and the improvement of total factor productivity in the value chains, but the val-ue chains typically suffer from low efficiency in the use of information technology.
Keywords: D24; L16; L23; M11; 330; Construction; Productivity; Global value chains; Organization of production; Production management; Industrial structure and structural chan